Illegal street hawkers issue facing the local authorities in Sarawak: a case study of urban streets in Kuching City / Noni Harianti Junaidi and Anisa Safiqah Othman - Junaidi, Noni Harianti; Othman, Anisa Safiqah (Universiti Teknologi MARA, Kedah, 2021)
Street hawking is an urban phenomenon in both developed and developing countries around the world. Several plans and strategies have been developed by the local authorities to address issues arising from hawking activities. There is no exception for the urban local authorities in Kuching City; the Kuching North City Hall (DBKU) and Kuching South City Council (MBKS). Illegal hawking has led to problems such as traffic congestion, littering and endangered formal entities. The problems that arise from the growth of illegal hawkers produced a negative image of urbanisation growth in the city. In this study , qualitative methods are used and data is collected using structured interviews. In order to identify the problems of illegal hawkers, officers from related departments at DBKU and MBKS were interviewed. The research identified several problems often faced by local authorities in the management of illegal hawkers, such as the resistance of hawkers to change to formal entities, the maintenance of the city's aesthetic value, the management of waste disposal, and consumer preferences. The study will hopefully help the local authorities to improve the management of hawkers in the cities. It is therefore intended to focus on the local authorities' problems in managing the growth of illegal hawkers in Kuching City and thus having an in-depth understanding of the nature of law and enforcement.